MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI MEREMAS ADONAN PADA ANAK TUNAGRAHITA RINGAN - Yulian - Sartika (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was motivated by the problems that researchers in the field discovered that mild mental retardation in a child's kindergarten class B (TK-up) to crash in fine motor skills. From the assessment results impaired child in school activities such as holding a pen, mimic the shape of circles, triangles, rectangles, Meems free paper and tore ketas patterned. Thus the researcher seeks help to improve fine motor skills through a child's fingers squeezing the dough. This study aims to improve fine motor skills mild mental retardation kindergarten children in SLB YPPA Padang. This research is Single Subject Research (SSR) with the reasons children studied single or single. Step-by-step use of SSR is done under different conditions using AB design. where A is the baseline conditions of the initial condition in the child's fine motor skills before being given action. While the condition B is the intervention conditions under which children were given dough squeezed through exercise intervention. The results of this study shows that children develop fine motor skills mild mental retardation kindergarten class at SLB YPPA Padang given exercises to increase after assuring the dough. This is evident when the observations were conducted in two sessions, the first session before granted intervention baseline (A) were performed five times of observation, and the percentage of fine motor skills in this condition lies in the range of 0%, 0%, 0%, 0% and 0%. Second, the intervention sessions (B) by using a dough kneading exercises, observations carried eight times of observation, and the percentage of children develop fine motor skills mild mental retardation in this condition lies in the range, 22.22% .22,22%, 50%, 50% , 72.22%, 72.22%, 100%, 100%. Based on the results of this study can be interpreted that the child's fine motor mild mental retardation kindergarten class SLB YPPA Padang can be increased through exercise squeezing the dough.